Coping in the Face of Verbal Aggression: The Role of Self-Efficacy in Protecting Healthcare Professionals’ Well-Being and Job Satisfaction - Elena Cavallari; Ilaria Setti; Matteo Curcuruto; Valentina Sommovigo (Behavioral Sciences)
Verbal aggression toward healthcare professionals, primarily from patients and visitors, is widespread and negatively affects employee well-being and patient care quality. This study, comprising two samples, investigates the relationship between user-initiated verbal aggression and job satisfaction, with a focus on psychological processes (i.e., cynicism and mental distance) and personal boundary conditions (i.e., self-efficacy). Study 1 (pandemic period) explored cynicism and work-related self-efficacy, while Study 2 (post-pandemic) replicated and expanded these findings, incorporating mental distance, self-efficacy in managing negative emotions, and workload. Participants included 201 (Study 1) and 1442 (Study 2) healthcare professionals from one and eight Italian healthcare facilities, respectively, who completed online questionnaires. In both cross-sectional studies, verbal aggression was positively associated with psychological withdrawal responses, which, in turn, was negatively related to job satisfaction. However, high self-efficacy in managing negative emotions (rather than work-related self-efficacy) buffered these effects. In Study 2, the negative impact of verbal aggression on job satisfaction, mediated by mental distance, was most pronounced among those with low self-efficacy in managing negative emotions and a high workload. Conversely, individuals with high self-efficacy maintained their job satisfaction and did not exhibit psychological withdrawal, even under high workload conditions.